Endotoxin and cytokines decrease serum levels and extra hepatic protein and mRNA levels of cholesteryl ester transfer protein in syrian hamsters. - Hardardóttir, I (1996)
Endotoxin alters the metabolism of lipoproteins, including that of high density lipoprotein (HDL). Cholesteryl ester transfer protein (CETP) facilitates exchange of HDL cholesterol for very low density lipoprotein (VLDL) triglyceride, leading to catabolism of HDL. We investigated the effects of endotoxin and cytokines on CETP in Syrian hamsters. Endotoxin induced a rapid and progressive decrease in serum CETP levels, by 48 h CETP had decreased to < 20% of control levels. Endotoxin also decreased CETP mRNA and protein levels in adipose tissue, heart, and muscle, the tissues with highest levels of CETP mRNA, providing a plausible mechanism for the endotoxin-induced decrease in circulating CETP. Dexamethasone did not mimic the effects of endotoxin on CETP, but the combination of tumor necrosis factor and interleukin-1 did, indicating that these cytokines may in part mediate the effects of endotoxin on CETP. The endotoxin-induced decrease in CETP may help maintain HDL cholesterol levels during infection and inflammation when increased triglyceride levels could drive the exchange of HDL cholesteryl ester for VLDL triglyceride. Maintaining circulating HDL may be important because HDL protects against the toxic effects of endotoxin and provides cholesterol for peripheral cells involved in the immune response and tissue repair.